PENGARUH KEPUASAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PERUSAHAAN AIRNAV INDONESIA - Yuli Anggraini; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
One of the main determinants that influence the success rate of a company is employee performance. Efforts to improve employee performance, including by pay attention to work satisfaction and competence. This research was aimed to determine the effect of work satisfaction and competence to employees performance of AirNav Indonesia company. The population in this research were employess of AirNav Indonesia company at financial department were amounted to 387 people. The sample in this study were amounted to 80 employees using Slovin formula with random sampling technique. The method of data technique which used in the research was using multiple linear regression analysis, coefficient of determination and hypothesis test. Before being analyzed the instrument test was carried out. The results of this research can be known that work satisfaction and competence have a positive and significant influence to employees performance of AirNav Indonesia company.